The culture of quality established by AVEPRO in ecclesiastical faculties. A spanish perspective - Uríbarri Bilbao, SJ, Gabino (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
The ecclesiastical faculty’s mission is to evangelize culture. such a mission cannot be accomplished in European campuses without implementing internal quality assurance procedures, as stipulated by the bologna process, to which the Holy see, for good reasons, adheres. Within the process of creation of a common European Higher education area (the key aspects of which are briefly outlined), AVEPRO, the Holy see’s agency for the evaluation and promotion of Quality in ecclesiastical universities and faculties, assumes the task of developing this culture of quality within the european higher education institutions that depend directly on the Holy see. this is does through promotion, not accreditation or verification. an internal quality assurance body, self-evaluation methods, external evaluation coupled with public reporting and an improvement plan open to review are all essential elements and all must be compliant with current European directives.
Keywords: Teaching; Quality; bologna; evangelising culture.